[tex]\begin{cases}1-\frac{x-1}{2}=2+\frac{y+1}{3}\ \ |*6\\x+y+4=0\end{cases}\\\\\begin{cases}6- 3(x-1)=12+2(y+1)\\x+y+4=0\end{cases}\\\\\begin{cases}6- 3 x+3=12+2 y+2\\x=-y-4 \end{cases}\\\\\begin{cases}9- 3 x =14+2 y \\x=-y-4 \end{cases} \\\\\begin{cases}9- 3 (-y-4) =14+2 y \\x=-y-4 \end{cases}[/tex]
[tex]\begin{cases}9+3y+12 =14+2 y \\x=-y-4 \end{cases}\\\\\begin{cases}21 +3y =14+2 y \\x=-y-4 \end{cases}\\\\\begin{cases}3y-2y =14-21 \\x=-y-4 \end{cases} \\\\\begin{cases} y =-7 \\x=7-4 \end{cases} \\\\\begin{cases} y = -7 \\x=3\end{cases}[/tex]